Evaluating Negative Attributions in Persons With Brain Injury: A Comparison of 2 Measures. Issue 3 (13th May 2021) - Neumann, Dawn; Sander, Angelle M.; Witwer, Noelle; Jang, Jeong Hoon; Bhamidipalli, Surya Sruthi; Hammond, Flora M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To compare construct and predictive validity, readability, and time-to-administer of 2 negative attribution measures in participants with traumatic brain injury (TBI). Setting: Two TBI rehabilitation hospitals. Participants: Eighty-five adults with complicated mild to severe TBI. Main Measures: Negative attributions (intent, hostility, and blame) and anger responses to hypothetical scenarios were measured with the Epps scenarios and the Ambiguous Intention Hostility Questionnaire (AIHQ). Trait aggression was measured with the Buss-Perry Aggression Questionnaire (BPAQ). Results: Associations between attributions and anger responses (ie, construct validity) within each measure were significant (Epps: r = 0.61-0.74; AIHQ: r = 0.39-0.71); however, associations were stronger for Epps ( P s < .001). Receiver operating characteristics (ROC) revealed attributions from both measures predicted BPAQ scores (area under the ROC curves = 0.6-0.8); predictive validity did not statistically differ between the 2 measures. Both had comparable readability (fifth- to sixth-grade levels), but Epps required longer administration times. Conclusion: Negative attributions affect anger and aggression after TBI, making it important to identify suitable assessments for the TBI population. While psychometric properties of the AIHQ and Epps scenarios should be further explored, this study offers early support for the use of either instrument in persons with TBI. Advantages and disadvantages of the AIHQ and Epps scenarios are highlighted.